2022
DOI: 10.3389/fmed.2022.846300
|View full text |Cite
|
Sign up to set email alerts
|

Highlights of Strategies Targeting Fibroblasts for Novel Therapies for Rheumatoid Arthritis

Abstract: Synovial fibroblasts of rheumatoid arthritis (RA) play a critical role in perpetuation of chronic inflammation by interaction with immune and inflammatory cells and in cartilage and bone invasion, but current therapies for RA are not directly targeted fibroblasts. Selectively fibroblast targeted therapy has been hampered because of lack of fibroblast specific molecular signature. Recent advancement in technology enabled us to gain insightful information concerning RA synovial fibroblast subpopulations and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“…In addition to the epigenetic machinery, strategies that target the imbalanced metabolic pathways in both RA SFs and CAFs have been employed to reduce RA severity and inhibit tumour growth respectively (158,159)). Interestingly, a recent study proposes a new strategy to control fibrosis and hypertrophic scars formation using an anti-glycolytic agent that regulates fibroblasts activity (160).…”
Section: Therapeutic Perspectives Of Targeting Fibroblasts In Inflamm...mentioning
confidence: 99%
“…In addition to the epigenetic machinery, strategies that target the imbalanced metabolic pathways in both RA SFs and CAFs have been employed to reduce RA severity and inhibit tumour growth respectively (158,159)). Interestingly, a recent study proposes a new strategy to control fibrosis and hypertrophic scars formation using an anti-glycolytic agent that regulates fibroblasts activity (160).…”
Section: Therapeutic Perspectives Of Targeting Fibroblasts In Inflamm...mentioning
confidence: 99%
“…22 First, similar to rheumatoid arthritis synovial fibroblasts (RASFs) in RA, ASFs can cause certain pathological responses in diseases by regulating factor secretion, coordinating inflammatory responses, regulating tissue homeostasis, and mediating joint remodeling. Currently, fibroblast research in RA is well-established, 23 with key findings in fibroblast subpopulations, fibroblast interactions, 18 and fibroblast-targeted therapies, 24,25 among others. AS and RA are autoimmune diseases with significant differences but certain similarities, especially in inflammation.…”
Section: Fibroblasts In Asmentioning
confidence: 99%
“…This showed the involvement of a broad range of cytokines but not of a single one [ 10 ]. It is suggested that HK is the target of the RASF-specific strategy for the RA-specific glycolysis regulation because HK is highly expressed in the RASF [ 8 , 15 ].…”
Section: Glucose Metabolism Shifts To Glycolysis In Rheumatoid Synoviummentioning
confidence: 99%